The development of engineering TVET instructor standard teaching competency framework for vocational college - Omar, Muhd Khaizer; Ismail, Khamsiah; Abdullah, Arnida; How, Shwu Pyng (Primrose Hall Publishing Group, 2021)
Individual competency consists of a set of knowledge, skills and personnel characters to execute specific responsibilities and designated tasks. A competent person upholds the highest integrity and ensures perfection to fulfill self-satisfaction and meeting the standard. Competency can be classified into myriad components, known as generic and specific skills. In light of the daunting issues on lack of skills among graduates claimed by the industries, Technical and Vocational Education and Training (TVET) educators have been pointed out to resolve the issue. The key aspect discussed on TVET instructor competency components is to empower graduates' employability. Thus, TVET instructors are requested to comply with the necessity to upgrade their theoretical and practical knowledge content and become adroit to compensate for the 21st- century teaching and learning environment. Emphasizes are from the development of teacher professional characteristics and specific competency traits in pedagogical aspects as well as soft skills training to synchronize with the ever changing educational milieu. This research employed a qualitative strand of a case study by compiling the narrative collected from the structured interview to obtain research data. The participants were selected among teachers, students, and vocational college directors in Selangor, Malaysia. The objective of the study is to explore the required competency components of the TVET instructors in engineering-related courses. The data was compiled using NVivo software and thematically analyzed by extracting and determining the ‘meaning-making process’ of participants to answer the formulated research questions. The findings of the study incited personality and values, ethics and professional practices, knowledge-development, professional skills, effective management, socializing skill, and pedagogical skill as pivotal themes emerged from the analysis. It is hoped that the findings will initiate a significant impact particularly to the Engineering TVET instructors at the vocational colleges. More importantly, it is to execute the competency components and drive instructors’ motivation to remain in the teaching profession and enhance the quality of TVET education as well as demonstrate professionalism among instructors.